2016
DOI: 10.1038/oncsis.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

A serum-circulating long noncoding RNA signature can discriminate between patients with clear cell renal cell carcinoma and healthy controls

Abstract: Serum biomarkers have not been fully incorporated into clinical use for the diagnosis of renal cell carcinoma (RCC). The recent discovery of long noncoding RNAs (lncRNAs), which have been reported in a variety of cancer types, suggested a promising new class of biomarkers for tumour diagnosis. The aim of our study was to evaluate whether the levels of circulating lncRNAs could be used as a tumour marker to discriminate between clear cell RCC (ccRCC) patients and healthy controls. Serum samples were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 42 publications
2
117
0
2
Order By: Relevance
“…In favor of this prospect, although no lncRNAs were reported in the bodily fluids of patient with OC, recent studies have identified elevated plasma lncRNA levels in patients with other cancer types such as non-small-cell lung cancer [83], hepatocellular carcinoma [84], thyroid cancer with lung metastases [85], esophageal squamous cell carcinoma [86], and renal cell carcinoma [87].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…In favor of this prospect, although no lncRNAs were reported in the bodily fluids of patient with OC, recent studies have identified elevated plasma lncRNA levels in patients with other cancer types such as non-small-cell lung cancer [83], hepatocellular carcinoma [84], thyroid cancer with lung metastases [85], esophageal squamous cell carcinoma [86], and renal cell carcinoma [87].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Numerous studies have reported that lncRNAs could be crucial players in cancer progression, particularly in terms of dysregulation of gene products that contribute to advanced human tumors [5][6][7]. Furthermore, lncRNAs could also be considered as diagnostic or prognostic markers due to their clinical association with tumor outcomes [8][9][10]. More recently, Pandolfi et al proposed a new regulatory mechanism in which all RNA transcripts harboring miRNA-binding sites can communicate and regulate each other's expression levels by competing specifically for shared miRNAs, thus acting as competing endogenous RNAs (ceRNAs) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has witnessed the discovery of diverse IncRNAs involved in physiological and pathological processes [8-12]. Many IncRNAs have been reported as important regulators in ccRCC, and several were also verified as biomarkers for early diagnosis and prognostic prediction for ccRCC [13, 14]. …”
Section: Introductionmentioning
confidence: 99%